2020
DOI: 10.21608/zvjz.2020.27091.1106
|View full text |Cite
|
Sign up to set email alerts
|

The Viability and Cytotoxic Effect of High Mobility Group Box Protein 1 on MC3T3-E1 Pre-osteoblast Cells: an In Vitro Study

Abstract: Osteoblast proliferation and migration are significantly involved in bone healing, regeneration and embryonic skeletal development. Recently, reports suggest anabolic properties of High Mobility Group Box Protein 1 (HMGB1) within the subsequent phase of tissue regeneration as well as HMGB1 has been shown to be highly expressed during bone fracture and regulates osteochondral ossification. In this study, the effect of various concentrations of Recombinant Human HMGB-1 (rhHMGB-1) (50, 100,150 and 200 µg/L) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…They applied a dose of 10 μg/defect of HMGB-1 in gelatin sponge scaffolds with mesenchymal stem cell sheets in a rat tibial osteotomy model. Although we recently showed that the maximum concentration of HMGB-1 was 150 μg/L for osteoblast viability in an in vitro study 50 , it remains to be elucidated whether 10 μg/defect of HMGB-1 is the maximum effective dose in vivo. In the present study, the volume of the remnant scaffold material was calculated using an image processing program.…”
Section: Discussionmentioning
confidence: 97%
“…They applied a dose of 10 μg/defect of HMGB-1 in gelatin sponge scaffolds with mesenchymal stem cell sheets in a rat tibial osteotomy model. Although we recently showed that the maximum concentration of HMGB-1 was 150 μg/L for osteoblast viability in an in vitro study 50 , it remains to be elucidated whether 10 μg/defect of HMGB-1 is the maximum effective dose in vivo. In the present study, the volume of the remnant scaffold material was calculated using an image processing program.…”
Section: Discussionmentioning
confidence: 97%